User generated content and its influence on relationship marketing among Generation Z - Dr. Anand Deshmukh , Dr. Tushar K. Savale, S Rahul, Dr. Amit A. Medhekar (Journal of Informatics Education and Research, 2024)
The post-millennial Generation Z, which was born into a technologically advanced society, is one of the most recent subjects in marketing. There are numerous companies with a wide range of products, and you are bombarded with advertisements from every direction. How then do you market to the most technologically advanced generation, whose focus is hard to get and who has higher expectations of you as a marketer than earlier generations? User generated material is one of the options you might consider (UGC).